Descrição da larva de último estádio de Oxyagrion sulmatogrossense Costa, Souza & Santos (Odonata, Coenagrionidae) - Dalzochio, Marina Schmidt (2010)
A larva de último estádio de Oxyagrion sulmatogrossense Costa, Souza & Santos 2000 é descrita e ilustrada a partir de material procedente de Cascavel, Paraná, Brasil. Description of the last instar larva of Oxyagrion sulmatogrossense Costa, Souza & Santos(Odonata, Coenagrionidae) Abstract. The last instar larva of Oxyagrion sulmatogrossense Costa, Souza & Santos 2000 is described and illustrated based on material collected in Cascavel Municipality, Paraná State, Brazil.